Appropriateness of using granulocyte colony-stimulating factor (G-CSF) for primary prophylaxis of febrile neutropenia in solid tumors. (March 2020) - Laali, Elahe; Fazli, Jinous; Sadighi, Sanambar; Mohammadi, Mehdi; Gholami, Kheirollah; Jahangard-Rafsanjani, Zahra
Introduction: Febrile neutropenia (FN) is one of the dose-limiting adverse effects of chemotherapy. Granulocyte-Colony Stimulating Factors (G-CSFs) minimize the incidence of FN and reduce the risk of neutropenia complications. This study was conducted to address the prescription pattern of G-CSF for primary prophylaxis of FN during the first cycle of chemotherapy in solid tumors. Method: This prospective observational study was done to investigate the G-CSF prescription pattern in patients receiving the first cycle of chemotherapy for solid tumors and compare it with the NCCN guideline recommendations. Result: Based on the guideline, prophylactic G-CSF administration was indicated in 26 of the 96 patients (27.1%) and all of them received G-CSF. On the other hand, 70 patients (72.9%) did not meet the guideline criteria for prophylaxis, but 60 (62.5%) of them received G-CSF. Seven doses of pegfilgrastim and 165 doses of filgrastim were used inappropriately in the study population, which was associated with an economic burden of about 224.7 million IRR (5350 USD). Conclusion: Taken together, inconsistencies with the guideline were observed in this prospective evaluation, suggesting that submitting rationalized policies to decrease G-CSF prescription, especially in patients with a lower or intermediate FN risk, yields substantial cost savings.